Aborigine rights to land: Malaysian and international laws perspective / Dalila Amir … [et al.] - Amir, Dalila; Mohamad Bahri, Nurwafa Atikah; Yusof, Mohamad Sabri; Che Jamaludin Mahmud, Izmi Izdiharuddin; Abdul Hadi, Khairul Anuar (Universiti Teknologi MARA, Pahang, 2022)
The aborigines in Malay Peninsula, which consist of three main tribes; Negrito, Senoi and Proto-Malay, from time in memory, had occupied and earned a living on land areas in the northern, central and southern regions of the Malay Peninsula. These aborigines can be divided into different tribe and sub-tribe communities, including, the Semai, Temiar, Lanoh, Bateq, Jakun, Kensiu, Jahai, Mendriq, Temuan, Semelai, Semai, Kintaq, Orang Kanaq, Orang Seletar and Mah Meri. Hence, the y are entitled to all the rights vested upon them, including the right to land. The assimilation process to integrate them cannot be realized without consulting their respective needs, especially rights to land. Ignoring these rights is tantamount to a violation of human rights. Thus, this paper intends to examine the rights provided for the aborigine under Malaysian and international laws to land.